Interpersonal affect in groupwork: A comparative case study of two small groups with contrasting group dynamics outcomes - Jones Cheryl; Volet Simone; Pino-Pasternak Deborah; Heinimäki Olli-Pekka (European Association for Research on Learning and Instruction (EARLI), 2022)
Teamwork capabilities are essential for 21st century life, with groupwork emerging as a fruitful context to develop these skills. Case studies that explore interpersonal affect dynamics in authentic higher education groupwork settings can highlight collaborative skills development needs. This comparative case-study traced the sociodynamic evolution of two groups of first-year university students to investigate the high collaborative variance outcomes of the two groups, which reported starkly contrasting group dynamics (negative and dysfunctional or positive and collaborative). Mixed-methods (video-recorded observations of five groupwork labs over one semester, and group interviews) provided interpersonal affect data as real-time visible behaviours, and the felt experiences and perceptions of participants. The study traced interpersonal affect dynamics in the natural fluctuation of not just task-focused (on-task), but also explicitly relational (off-task) interactions, which revealed their function in both task participation and group dynamics. Findings illustrate visible interpersonal affect behaviours that manifested and evolved over time as interactive patterns, and group dynamics outcomes. Fine-grained analysis of interactions unveiled interpersonal affect as a collective, evolving process, and the mechanism through which one group started and stayed highly positive and collaborative over the semester. The other group showed a tendency towards splitting to undertake tasks early, leading to low group-level interpersonal attentiveness, and over time, subgroups emerged through interactions both off-task and on-task. The study made visible the pervasive nature of interpersonal affect as enacted through seemingly inconsequential everyday behaviours that supported the relational and task-based needs of groupwork, and those behaviours which impeded collaboration.